2018
DOI: 10.1038/s41431-017-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

SHOX haploinsufficiency presenting with isolated short long bones in the second and third trimester

Abstract: Haploinsufficiency of the transcription factor short stature homeobox (SHOX) manifests as a spectrum of clinical phenotypes, ranging from disproportionate short stature and Madelung deformity to isolated short stature. Here, we describe five infants with molecularly confirmed diagnoses of SHOX haploinsufficiency who presented in utero with short long bones during routine antenatal scanning from as early as 19 weeks gestation. Other foetal growth parameters were normal. The molecular basis of SHOX haploinsuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…In the order of discussion, three rightmost columns of Table S 1 cite a clinical report [ 44 ] on SHOX deficiency as a known physiological marker of Madelung deformity and disproportionate short stature in newborns, as found in the PubMed database in its “Keyword search” mode [ 45 ] (hereinafter: see Supplementary Keyword Search, Additional file 3 ). That is why there is a down arrow (↓) in the “♂” column, which means a candidate SNP marker for a decrease in male reproductive potential, as predicted here, within the applicability limits described in ref.…”
Section: Resultsmentioning
confidence: 99%
“…In the order of discussion, three rightmost columns of Table S 1 cite a clinical report [ 44 ] on SHOX deficiency as a known physiological marker of Madelung deformity and disproportionate short stature in newborns, as found in the PubMed database in its “Keyword search” mode [ 45 ] (hereinafter: see Supplementary Keyword Search, Additional file 3 ). That is why there is a down arrow (↓) in the “♂” column, which means a candidate SNP marker for a decrease in male reproductive potential, as predicted here, within the applicability limits described in ref.…”
Section: Resultsmentioning
confidence: 99%
“…SHOX deficiency should be considered if the family history shows an autosomal dominant inheritance pattern of disproportionate short stature (increased sitting height index or increased upper to lower body segment ratio), short 4 th metacarpal bones and/or Madelung deformity. Recently, Ramachandrappa et al reported that SHOX haploinsufficiency may be detected during routine antenatal ultrasound as early as 19-weeks of gestation [18]. However, it did not seem that antenatal presentation of SHOX haploinsufficiency was indicative of severe postnatal growth restriction [18].…”
Section: Monogenic Causes Of Isolated Short Staturementioning
confidence: 99%
“…Recently, Ramachandrappa et al reported that SHOX haploinsufficiency may be detected during routine antenatal ultrasound as early as 19-weeks of gestation [18]. However, it did not seem that antenatal presentation of SHOX haploinsufficiency was indicative of severe postnatal growth restriction [18].…”
Section: Monogenic Causes Of Isolated Short Staturementioning
confidence: 99%
“…The second group includes abnormalities that can only be seen with fetal maturation, such as certain malformations of cortical development, microcephaly or hydrocephaly, gastrointestinal abnormalities relating to intestinal obstruction, urinary tract abnormalities that change over time such as renal pelvis dilation and some skeletal dysplasias. [16][17][18][19][20] There are some important considerations when detecting abnormalities in late pregnancy. These include factors at the level of the individual, such as ensuring appropriate consent prior to growth scans; anxiety provoked given the limited time to carry out full investigations, and referral for appropriate fetal/neonatal care; and implications at the level of the health system, such as the need for efficient late referral pathways and the associated costs of growth screening.…”
Section: Introductionmentioning
confidence: 99%